Įžuvintų europinių ungurių (Anguilla anguilla L.) migracija Lietuvoje ir potencialus indėlis į nerštinių išteklių atkūrimą - Dainys, Justas (Institutional Repository of Vilnius University, 2017)
A steep decline in recruitment that commenced during the 1980s has resulted in abundance of the European eel population falling below safe biological limits. Nowadays, stocking of eels is one of the main actions implemented to restore stocks. This raises questions related to the efficacy of this intervention and whether persistence with this strategy can be considered to represent ‘best practise’. Results of the current study demonstrated that on-grown eels have no advantage in survival compared with glass eels when fed Chironomus spp. in the laboratory. After stocked eels reach silver eel stage and start their downstream migration substantial mortality can dramatically reduce the number of spawners if they were stocked upstream of a hydropower plant (HPP). CINK turbines were found to be causing 100% mortality, whereas in small and large Kaplan turbines mortality was 52 and 24%, respectively. If stocking is carried upstream HPP, then a fish ladder in combination with effective screening must be installed to reduce eel mortality. This study estimated that 34% of the migrating eels used it in order to bypass the HPP. Overall eel migration success in Lithuanian rivers and the Curonian Lagoon was 35%. The average eel migration speed in rivers was 11.7 km d-1 and 14.6 km d-1 in the Lagoon. Even though eels stocked into Lithuanian waters were shipped for more than 2000 km prior to their release, 37% of the silver eels migrating downstream accumulated sufficient energetic stores necessary for gonadal maturation and migration to the spawning grounds. The remaining 63% of the silver eels had a marginal shortage of energy resources. The implications of these results should be considered during any assessment of eel management strategies.